Improved parental dietary quality is associated with children's dietary intake through the home environment - K. R. Flórez; A. S. Richardson; M. B. Ghosh‐Dastidar; R. Beckman; C. Huang; L. Wagner; T. Dubowitz (Wiley, 2017)
Summary Background Improving access to supermarkets has been shown to improve some dietary outcomes, yet there is little evidence for such effects on children. Relatedly, there is a dearth of research assessing the impact of a structural change (i.e. supermarket in a former food desert) on the home environment and its relationship with children's diet. Objective Assess the relative impact of the home environment on children's diet after the introduction of a new supermarket in a food desert. Methods Among a randomly selected cohort of households living in a food desert, parental diet was assessed before and after the opening of a full‐service supermarket. The home environment and children's intake of fruits and vegetables was measured at one point - after the store's opening. Structural equation models were used to estimate the pathways between changes in parental dietary quality at follow‐up and children's dietary intake through the home environment. Results Parental dietary improvement after the supermarket opened was associated with having a better home environment (β = 0.45, p = 0.001) and with healthier children's dietary intake (β = 0.46, p < 0.001) through higher family nutrition and physical activity scores (β = 0.25, p = 0.02). Conclusions Policy solutions designed to improve diet among low‐resource communities should take into account the importance of the home environment.